2008
DOI: 10.1007/s00467-007-0734-5
|View full text |Cite
|
Sign up to set email alerts
|

Global left-ventricular function by tissue Doppler imaging in pediatric dialysis patients

Abstract: Cardiovascular abnormalities are observed in most children with end-stage renal disease (ESRD). The aim of this study was evaluation of left-ventricular (LV) myocardial performance using tissue-Doppler imaging (TDI) in patients with ESRD. Twenty-five patients with ESRD and 25 healthy gender- and age-matched control subjects were assessed with conventional M-mode echocardiography, pulsed-wave Doppler (PWD), and TDI. Myocardial Performance Index (MPI) and LV mass index (LVMI) were calculated. MPI and conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 35 publications
5
29
1
Order By: Relevance
“…[6][7][8][9] Conventional PWD has been widely used to assess LV diastolic function and, in this method, a decrease in the E/A ratio, the index of LV relaxation, indicates diastolic dysfunction. In previous studies, reduced E/A ratios in children on dialysis have often been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[6][7][8][9] Conventional PWD has been widely used to assess LV diastolic function and, in this method, a decrease in the E/A ratio, the index of LV relaxation, indicates diastolic dysfunction. In previous studies, reduced E/A ratios in children on dialysis have often been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, reduced E/A ratios in children on dialysis have often been reported. 7,8,18,19 In addition, Mitsnefes et al 6 determined low E/A ratios in predialysis pediatric patients as well. Whereas, in another studies in CKD patients, E/A ratios were similar to that in healthy children, in contrast to Mitsnefes et al 9, 10 We also did not find any significant difference in E/A ratios between the patient and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LVH has been reported in 20-50 percent of children with stage 2-4 CKD [33][34][35] and the prevalence increases over time. [36] The prevalence is even higher in dialysis [37][38][39] and transplant [40][41][42][43] patients, and results are mixed in terms of whether LVH improves with either form of renal replacement therapy. Both concentric and eccentric LVH are commonly described in all stages of CKD.…”
Section: Evidence Of Early Cardiomyopathymentioning
confidence: 98%